Amino acid-derived N-heterocyclic carbene palladium complexes for aqueous phase Suzuki–Miyaura couplings. (4th April 2016) - Steeples, Elliot; Kelling, Alexandra; Schilde, Uwe; Esposito, Davide
Abstract : Five palladium complexes featuring N-heterocyclic carbene ligands derived from sustainable precursors have been synthesized and applied in aqueous Suzuki–Miyaura couplings. Abstract : In this work, three ligands produced from amino acids were synthesized and used to produce five bis- and PEPPSI-type palladium–NHC complexes using a novel synthesis route from sustainable starting materials. Three of these complexes were used as precatalysts in the aqueous-phase Suzuki–Miyaura coupling of various substrates displaying high activity. TEM and mercury poisoning experiments provide evidence for Pd-nanoparticle formation stabilized in water.